A New Approach for the Approximations of Solutions to a Common Fixed Point Problem in Metric Fixed Point Theory - Ishak Altun; Nassir Al Arifi; Mohamed Jleli; Aref Lashin; Bessem Samet (Journal of Function Spaces)
We provide sufficient conditions for the existence of a unique common fixed point for a pair of mappings T,S:X→X, where X is a nonempty set endowed with a certain metric. Moreover, a numerical algorithm is presented in order to approximate such solution. Our approach is different to the usual used methods in the literature.